A review of advanced catalyst development for Fischer–Tropsch synthesis of hydrocarbons from biomass derived syn-gas - Jahangiri, Hessam; Bennett, James; Mahjoubi, Parvin; Wilson, Karen; Gu, Sai (Royal Society of Chemistry (RSC), 2014)
Fischer–Tropsch synthesis (FTS) is a process which converts syn-gas (H2 and CO) to synthetic liquid fuels and valuable chemicals. Thermal gasification of biomass represents a convenient route to produce syn-gas from intractable materials particularly those derived from waste that are not cost effective to process for use in biocatalytic or other milder catalytic processes. The development of novel catalysts with high activity and selectivity is desirable as it leads to improved quality and value of FTS products. This review paper summarises recent developments in FT-catalyst design with regards to optimising catalyst activity and selectivity towards synthetic fuels.